2004
DOI: 10.1021/jo049762t
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated Reactions of Vinyl Phosphate Esters with Triorganostannides. Evidence for an SRN1 Vinylic Mechanism

Abstract: Ketones are converted into vinyl diethyl phosphate esters (VinDEP), which under photostimulation reacted with sodium trimethylstannide (1) or sodium triphenylstannide (2) in liquid ammonia affording vinylstannanes via a vinylic S(RN)1 mechanism. Thus, (1-phenylvinyl)DEP (3), (3,4-dihydro-1-naphthyl)DEP (7), (3,4-dihydro-2-naphthyl)DEP (9), (E)-(1,2-diphenylvinyl)DEP (12), (E/Z)-(1-methyl-2-phenylvinyl)DEP (14) and (E)-(1-phenyl-2-methylvinyl)DEP (16) react with 1 and 2, under photostimulation, leading to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It should be mentioned that not only the substrate structure but also the nature of the anion are essential factors for the prevalence of an S RN 1 vinylic route over ionic pathways and it is necessary an appropriate combination of both [3][4][5][6]. Thus, only vinyl systems supporting, at least, a phenyl group afforded the substitution product by S RN 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be mentioned that not only the substrate structure but also the nature of the anion are essential factors for the prevalence of an S RN 1 vinylic route over ionic pathways and it is necessary an appropriate combination of both [3][4][5][6]. Thus, only vinyl systems supporting, at least, a phenyl group afforded the substitution product by S RN 1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the anion basicity prevails over its reducing character the presence of both vinylic and allylic hydrogen(s) should be avoided. Recently, we have demonstrated that the diethoxyphosphoryloxy group can act as an excellent nucleofuge in the reaction of aryl phosphate esters [7] as well as vinyl diethyl phosphate esters (vinylDEP) [4], with trimethyl-and triphenyltin anions in liquid ammonia under irradiation, and that these reactions take place through an S RN 1 mechanism. Because of the reducing character of organotin anions [8] the S RN 1 mechanism prevails over ionic routes even with substrates containing vinylic and allylic hydrogen(s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In connection with the synthetic importance of these reactions, we are interested in searching new routes to aryl-and vinylstannanes. Thus, application of S RN 1 reactions [3] to the synthesis of aryl- [4] and vinylstannanes [5] is currently in progress in our laboratory. This alternative route to the synthesis of organostannanes avoids the use of Grignard reagents or organolithium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…9 For the above exposed reasons, DECP has received added interest as phosphorylating reagent, in organic and bioorganic chemistry such as: synthesis of structurally specific olefins, 1a,b,10 synthesis of acetylenes, 11 synthesis of phosphonates 12 and bisphosphonates, 13 selective synthesis of thiol esters, 14 cross-coupling reactions in the presence of various heteroatoms, 15,1d industrial scale synthesis of vinyl halides, 16 displacement of phosphate as leaving group 17 by an anion (e.g. organotin 18 or tellurolate 19 anions) or by alkyl cuprates. 20 DECP is commercially available.…”
Section: Introductionmentioning
confidence: 99%